Effects of Preoperative Pregabalin On Postoperative Pain Control in Total Knee Arthroplasty Surgery. Issue 8 (22nd July 2021) - Akdoğan, Mutlu; Ütebey, Gülten; Atilla, Halis Atıl; Öztürk, Alper; Çatma, Mehmet Faruk
Abstract: Objective: Pain management is a major component of postoperative patient care. Pain management following total knee arthroplasty (TKA) provides patient comfort and early mobilization and prevents serious complications. The present study aimed to evaluate the effects of preoperative administration of oral pregabalin on postoperative pain control in patients undergoing TKA. Methods: One hundred and twenty-six patients undergoing TKA were retrospectively included, of whom 65 (51.6%) received 150 mg pregabalin 2 hours before the operation and 61 (48.4%) did not. All patients received the same postoperative pain management protocol. Resting pain was recorded using a visual analog scale (VAS) at the postoperative 4th, 12th, and 48th hours. Findings including headache, dizziness, nausea-vomiting, constipation, dry mouth, pruritus, urinary retention, and sleepiness were recorded. Results: The mean age of 126 patients (84.1% female) was 65.5 ± 4.5 years (range, 55–72 years). No significant differences were found in age, sex, ASA score, and operation duration between the groups. VAS scores at the postoperative 4th, 12th, and 48th hours, frequency of pushing the button of PCA system, and the total tramadol dose were significantly lower in the pregabalin group. The percent decrease in the postoperative VAS scores from the 4th hour to the 48th hour was significant in the pregabalin group. Nausea was the most frequent side effect followed by urinary retention, constipation, and pruritus. Conclusion: Preoperative pregabalin administration provided a favorable contribution to the postoperative pain management in the patients undergoing TKA. Preoperative pregabalin administration could reduce opioid drug usage and opioid related side effects.